2022
DOI: 10.5155/eurjchem.13.2.162-167.2231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcination temperature on the structure and morphology of zinc oxide nanoparticles synthesized by base-catalyzed aqueous sol-gel process

Abstract: This study reports the base-catalyzed aqueous sol-gel synthesis of zinc oxide nanoparticles. The solution was primarily comprised of zinc nitrate hexahydrate as a metal precursor, isopropyl alcohol and water as solvents, and glycerin as a stabilizing agent. The effect of calcination temperature on the structure and morphology of the prepared nanoparticles was investigated by varying the calcination temperature from 500 to 900 °C. The X-ray diffraction analysis, infrared spectroscopy, thermogravimetric analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The micrograph for ZNA-3 (Fig. 5 b) also illustrates irregular morphology however, the particles appear to be larger in size as compared to ZNA-1 due to the particle growth at higher calcination temperatures [ 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The micrograph for ZNA-3 (Fig. 5 b) also illustrates irregular morphology however, the particles appear to be larger in size as compared to ZNA-1 due to the particle growth at higher calcination temperatures [ 35 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The micrograph for ZNA-3 (Fig. 4b) also illustrates ake-like morphology however, the akes appear to be larger in size as compared to ZNA-1 due to the particle growth at higher calcination temperatures [27].…”
Section: Field Emission Scanning Electron Microscopymentioning
confidence: 94%
“…The samples were prepared via a co-precipitation method and dried overnight at 150 • C, and the powder was obtained by mechanical grinding. Another study reported the effect of calcination temperature on the structure and morphology of ZnO nanoparticles [25]. The agglomeration increased with calcination at 500 • C, but as the temperature rose, there was a notable decrease in agglomeration as a result of nanoparticle separation.…”
Section: Introductionmentioning
confidence: 99%